Zionism, Pan-Asianism, and the Postcolonial Predicament in the Interwar Writings of Eugen Hoeflich - Rubín, Abraham (AJS review, 2021)
In the early 1920s, the Viennese writer and journalist Eugen Hoeflich promoted a unique vision of Zionism that aligned Jewish nationalism with a set of anticolonial ideologies collectively known as Pan-Asianism. This article explores the poetic and political strategies Hoeflich employed in order to affiliate Zionism with the Pan-Asian idea in general, and the Indian anticolonial struggle in particular. I read Hoeflich's turn to Pan-Asianism as an attempt to work through a conceptual problem that theorist Partha Chatterjee calls the “postcolonial predicament.” That is, how might the Jews assert their collective identity without reproducing the Eurocentric discourses that presuppose their inferiority? Hoeflich's vision of Indian-Jewish solidarity constitutes an imaginative effort to de-Europeanize Jewish nationalism and disentangle Zionism from British imperial designs. On a broader level, this study sheds light on the transnational solidarities that informed central European Zionists in the interwar era, and points to the discursive continuities that linked Jewish nationalists in Europe to anticolonial thinkers in Asia.